Application and research of nano-biomaterials in the rehabilitation of sports tendon rupture. (2nd April 2021) - Bai, Suping; Zhao, Ligong
Nano-biomaterials have important application and development in the field of tendon fracture rehabilitation. However, with the continuous improvement of people's requirements for tendon repair, the traditional single biomaterials are difficult to meet the actual needs of tendon repair, so the biomaterials have gradually developed. Biocomposites often have the comprehensive advantages of two or more materials, which can achieve optimal and purposeful tissue repair. In this paper, the effects of nanocomposites with dual functions of tendon regeneration and barrier on the rehabilitation of exercise-induced tendon rupture will be studied. In this paper, nanowire/polylactic acid double-sided synthetic materials are mainly used in the actual preparation of biomaterials. Its main purpose is to overcome the contradiction between tendon-induced suture and adhesion of surrounding tissues in the process of tendon repair of traditional biomaterials. In the experimental part of this paper, based on the tendon rupture of a patient, the Achilles tendon suture experiment was carried out with the mixed biomaterials proposed in this paper. The experiment shows that the comprehensive biomaterials proposed in this paper have obvious rehabilitation advantages.